Limited and Varying Consumer Attention: Evidence from Shocks to the Salience of Bank Overdraft Fees - Stango, Victor; Zinman, Jonathan (Review of Financial Studies, 2014)
We explore dynamics of limited attention in the $35 billion market for checking overdrafts, using survey content as shocks to the salience of overdraft fees. Conditional on selection into surveys, individuals who face overdraft-related questions are less likely to incur a fee in the survey month. Taking multiple overdraft surveys builds a “stock” of attention that reduces overdrafts for up to two years. The effects are significant among consumers with lower education and financial literacy. Individuals avoid overdrafts by making fewer low-balance debit transactions and cancelling automatic recurring withdrawals. The results raise new questions about consumer financial protection policy.